2006
DOI: 10.1080/00365540600606556
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii in Sweden, Estonia and Iceland

Abstract: Background: Toxoplasmosis is a disease caused by the intracellular protozoan parasite,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 22 publications
3
29
2
Order By: Relevance
“…Two previous studies have reported that T. gondii seropositivity is associated with higher CRP level (Birgisdóttir et al, 2006; Hinze-Selch et al, 2007), which has also been observed in a mouse model of chronic T. gondii infection (Tomasik et al, 2016). Elevated CRP, in turn, may predispose to depressive symptoms (Valkanova et al, 2013).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Two previous studies have reported that T. gondii seropositivity is associated with higher CRP level (Birgisdóttir et al, 2006; Hinze-Selch et al, 2007), which has also been observed in a mouse model of chronic T. gondii infection (Tomasik et al, 2016). Elevated CRP, in turn, may predispose to depressive symptoms (Valkanova et al, 2013).…”
Section: Discussionmentioning
confidence: 62%
“…A previous Nordic study has found that T. gondii seropositivity is associated with higher values of C-reactive protein (CRP) (Birgisdóttir et al 2006), which in turn is associated with both depression (Young et al, 2014) and anxiety (Copeland et al, 2012). Therefore, we investigated whether associations between mental health and T. gondii seropositivity changed after adjusting for CRP level.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the decrease observed in other countries ( Jones et al 2007, Pappas et al 2009, Villena et al 2010, there has been no decline in T. gondii seroprevalence in humans in Estonia (Pehk 1994, Birgisdottir et al 2006, Janson et al 2013. The reasons for this have not been studied.…”
Section: Introductionmentioning
confidence: 76%
“…Our findings agree with those reports of lower prevalence of T. gondii infection in atopic patients compared to non-atopics [15-17,20,21], reinforcing the hypothesis that a higher exposure to T. gondii reduces sensitization on population level. On the other hand, other studies did not find any association between seropositivity to T. gondii and atopy [14,18,19]. One likely explanation for these contradictory findings may be the selection criteria used for definition of atopy [21], since the prevalence of respiratory allergic diseases increases linearly with the increase in specific serum IgE levels [22].…”
Section: Discussionmentioning
confidence: 99%